2020
DOI: 10.1186/s40164-020-00179-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metabolic reprogramming by tumor suppressor genes in pancreatic cancer

Abstract: Background: Pancreatic cancer continues to be one of the most aggressive malignant tumors. Work in recent years in cancer molecular biology has revealed that metabolic reprogramming is an additional hallmark of cancer that is involved in the pathogenesis of cancers, and is intricately linked to gene mutations. Main text: However, though oncogenes such as KRAS and c-Myc play important roles in the process, and have been extensively studied, no substantial improvements in the prognosis of pancreatic cancer have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 123 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…Other tumor suppressors frequently mutated in cancer cells have been linked to the altered cellular metabolism of various types of cancer, including PDAC ( 18 ). A homozygous deletion of the tumor suppressor gene locus SMAD4, which occurs in PDAC and can cause the loss of the malic enzyme 2 (ME2), was previously exploited to disrupt NADPH production, mitochondrial redox homeostasis and amino acid metabolism.…”
Section: Amino Acids Are Involved In the Regulation Of Pancreatic Can...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other tumor suppressors frequently mutated in cancer cells have been linked to the altered cellular metabolism of various types of cancer, including PDAC ( 18 ). A homozygous deletion of the tumor suppressor gene locus SMAD4, which occurs in PDAC and can cause the loss of the malic enzyme 2 (ME2), was previously exploited to disrupt NADPH production, mitochondrial redox homeostasis and amino acid metabolism.…”
Section: Amino Acids Are Involved In the Regulation Of Pancreatic Can...mentioning
confidence: 99%
“…Alternative strategies to combat this lethal disease are therefore sought after and the targeting of the deregulated metabolic physiology, which is additionally connected to radio- and chemo-resistance in PDAC, is one of the promising options ( 16 , 17 ). The common genomic alterations, such as the activation of the KRAS oncogene, the deletion of the tumor suppressor gene, SMAD4, or the transformation of the tumor suppressor, p53, into a prooncogenic protein significantly stimulate nutrient acquisition and a variety of metabolic pathways ( 18 ). The ability to stratify PDAC tumors into subgroups with distinct metabolic requirements and vulnerabilities could offer valuable prognostic information and may aid to in the selection of specific treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of chemokine receptors, particularly chemokine (C–C motif) receptor 4 (CCR4), CCR7, CCR8, C–X–C chemokine receptor type 4 (CXCR4), and CXCR5 [ 19 , 20 ], contributes to the abundant accumulation of Tregs in the TME, where they are metabolically reprogrammed and functionally adapted to the low-nutrient, high-lactate environment. It is widely acknowledged that cellular metabolic reprogramming is a hallmark of cancer [ 1 , 21 ]. Furthermore, manipulation of cellular metabolism on the viability and function of both cancer cells and immune cells has aroused growing concern in the past decade, and considerable efforts have been made in checkpoint blockade immunotherapy and adoptive cellular treatment [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous group 25 classified multiple tumors, such as ovarian cancer, 26 hepatocellular carcinoma, 27 and pancreatic cancer, 28,29 into different metabolic subgroups according to various metabolic pathways. Qian et al 15 identified two clusters and a three lipid metabolism‐related gene prognosis model for OS.…”
Section: Introductionmentioning
confidence: 99%